Pemberdayaan Masyarakat Pesisir Berbasis Pengembangan Potensi Desa Mantang Lama, Di Kabupaten Bintan: Pemberdayaan Masyarakat Pesisir Berbasis Pengembangan Potensi Desa Mantang Lama, Di Kabupaten Bintan - Saputri; Fauziah Dwi Putri; Ozy Mustari; Ahmad Riyadi; Siti Khatijah; Sri Wahyuni (UNIB Press, 2024)
This study aims to look at how to develop the potential and empowerment of the community of Mantang Lama Village in improving community welfare and to see the level of community participation in developing this potential. This study uses a qualitative method with a descriptive approach. The data collection technique uses observation and interview techniques. Use secondary and primary data sources. The data analysis is carried out in three stages: data reduction, data presentation, and conclusion. The informants were determined using the purposive sampling technique. This research uses the social capital theory of Robert Putnam; in his theory, three elements are a reference for the success of empowerment. From the results of field findings in Mantang Lama Village, there are several potentials developed by BUMDes, namely five fishermen’s fishing vessels, the creation of mini food courts, and the provision of packing equipment and KUBE. However, it was also found that there was a lack of community participation in developing the potential of Mantang Lama Village. In conclusion, community participation in developing potential in Mantang Lama Village is essential to help the community's economy and increase Regional Original Income (PAD). Suggestions on the need for socialization from the management of BUMDes and being able to assist in providing training to improve community skills in managing potential in Mantang Lama Village.